Optically Activated 3D Thin‐Shell TiO2 for Super‐Sensitive Chemoresistive Responses: Toward Visible Light Activation. Issue 3 (3rd December 2020) - Cho, Donghwi; Suh, Jun Min; Nam, Sang‐Hyeon; Park, Seo Yun; Park, Minsu; Lee, Tae Hyung; Choi, Kyoung Soon; Lee, Jinho; Ahn, Changui; Jang, Ho Won; Shim, Young‐Seok; Jeon, Seokwoo
Abstract: One of the well‐known strategies for achieving high‐performance light‐activated gas sensors is to design a nanostructure for effective surface responses with its geometric advances. However, no study has gone beyond the benefits of the large surface area and provided fundamental strategies to offer a rational structure for increasing their optical and chemical performances. Here, a new class of UV‐activated sensing nanoarchitecture made of highly periodic 3D TiO2, which facilitates 55 times enhanced light absorption by confining the incident light in the nanostructure, is prepared as an active gas channel. The key parameters, such as the total 3D TiO2 film and thin‐shell thicknesses, are precisely optimized by finite element analysis. Collectively, this fundamental design leads to ultrahigh chemoresistive response to NO2 with a theoretical detection limit of ≈200 ppt. The demonstration of high responses with visible light illumination proposes a future perspective for light‐activated gas sensors based on semiconducting oxides. Abstract : The high‐performance light‐activated NO2 gas sensors using 3D TiO2 nanostructures are achieved by the unique light harvesting properties of the nanoporous structures. The light scattering effects from optical maze‐like nanostructures and numerous intermediate energy states from atomic layer deposition of the film electronically activate 3D TiO2 and enhance its gas sensing performance under UV illumination.